TINJAUAN SOSIOLOGIS TERHADAP NOVEL KAU CERAIKAN AKU, KUNIKAHI KAKAKMU DI FIZZO NOVEL KARYA REIN AZAHRA - Nida Urahmah (CV. Adiba Aisha Amira, 2024)
The objectives to be achieved in this research are: (1) to describe the sociological aspects of mimesis of literary works in the novel Kau Ceraikan Aku, Kunikahi Your Brother Di Fizzo, a novel by Rein Azahra, in terms of characters and characterization, social status, behavior of the characters, and events that occur. . This research is in the form of a sociological review of literature using qualitative methods. Research techniques include the stages of data collection, data analysis, data presentation, and drawing conclusions. The data sources consist of primary data (the novel Kau Diceraikan Aku, Kunikahi Your Sister Di Fizzo Novel by Rein Azahra) and secondary data in the form of literary books and other sources. The results of the research show that the sociological aspect of mimesis in the novel Kau Diceraikan Aku, Kunikahi Your Sister Di Fizzo, a novel by Rein Azahra, is an imitation of the situation of today's young people, where many young people do not like arranged marriages which end in affairs, because they look at appearance and physicality.